ANALISIS PENILAIAN TINGKAT KESEHATAN BANK MENGGUNAKAN METODE RGEC PADA BANK SYARIAH DI INDONESIA - Dwifa Putra Iskandar; Alvien Nur Amalia (Journal of Accounting, Management and Islamic Economics, 2025)
This research was conducted to analyse how the soundness level of Islamic banks both individually and as a whole. In conducting the assessment using the Risk Profile, Good Corporate Governance, and Capital (RGEC) method in accordance with POJK Number 10 ISEOJK 03 I 2014 concerning Rating of Soundness for Islamic Commercial Banks and Sharia Business Units. This RGEC is a change from the Capital, Assets, Management, Earning, Liquidity, and Sensitivity to Market Risk (CAMELS) by Bank Indonesia, because CAMELS is considered insufficient to provide a complete picture of how the bank is managed. The total number of Islamic banks studied was 14 Islamic commercial banks registered with the Financial Services Authority (OJK). Assessment of the Soundness Level of Islamic Commercial Banks both as a whole or Individually using the RGEC method, showing the results of the bank's soundness predicate in accordance with the standards set by the Financial Services Authority during the 2014-2019 period, it can be concluded that only Bank Aceh and Bank NTB Syariah get a rating composite with the conclusion 'Very Healthy" and for other Sharia Banks it only achieves "Sound", "Fairly Sound" and "Unhealthy". The soundness level of Islamic Commercial Banks is viewed from the aspects of the Risk Profile, GCG, Earnings, and Capital as a whole in Indonesia during the 2014-2019 period, predicated on a Healthy" conclusion.